Der Hund von Baskerville nach dem gleichnamigen Roman von Arthur Conan Doyle - Buchwald, Günter A.; Doyle, Arthur C. (Flicker Alley, 2020)
Richard Oswald's "Der Hund von Baskerville", the last silent film starring Sherlock Holmes, has been less a legend than a rumor among cinephiles and Sherlockians. This seven-reel film, with its long pedigree extending back to a German stage play written while Germany was at war with England, has been regarded as the most important of the "Hound" made in Europe. Long considered lost, it was the last silent Sherlock Holmes film ever made, produced when German studios were the envy of the world. Seen here in two versions, one with English titles and one entirely in German with titles based on the original German censor records, "Hund" lives again accompanied by a new ensemble score from the incomparable Günter Buchwald, Frank Bockius and Sascha Jacobsen. [www.flickeralley.com]